Pengembangan Bahan Ajar Menulis Teks Eksposisi dengan Menggunakan SAC pada Siswa Kelas X SMA - Permatasari, Ela; Kusmawati, Nurita Bayu; Purbarani, Etsa (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
This research aims to develop teaching materials for writing expository texts using Smart Apps Creator for class X students. This research uses the Research and Development (R&D) method. The development model used in this research is the ADDIE model. Data obtained from observations, interviews and questionnaires. The data processing techniques used are qualitative and quantitative. Product feasibility testing was carried out by material experts and media experts, as well as assessments by Indonesian language teachers and class X students at SMAN 72 Jakarta. The results of validation of teaching materials using Smart Apps Creator by material experts got an average score of 4.5 with a percentage of 90%, while media experts got an average score of 4,9 with a percentage of 98%, so it is included in the very worthy category. Furthermore, the assessment carried out by Indonesian language teachers received an average score of 4.9 with a percentage of 98% falling into the very decent category. The results of product development were tested on 28 students, getting an average score of 4.6 with a percentage of 93% falling into the very decent category. Based on this assessment, it can be concluded that the development of teaching materials for writing expository texts using Smart Apps Creator for class X SMA students is very suitable for use in the learning process.